Pseudohypoparathyroidism: A Case Report of a Rare Disease with Uncommon Presentation Producing Diagnostic Dilemma (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Pseudohypoparathyroidism (PHP) is a rare hereditary  disorder having the prevalence of 3.4 per million. It is  characterized by symptoms and signs of  hypoparathyroidism, typically in association with distinctive  skeletal and developmental defects. The features of  hypoparathyroidism are due to tissue resistance to the effect  of parathyroid hormone (PTH). We will describe a 32-yearold  woman who had recurrent convulsion for 16 years,  infertility, cataract, psychosis, candidiasis and typical  features of Albrights hereditary osteodystrophy (AHO),  which include a round face, short neck, short stature and  brachydactyly. Laboratory investigations showed  hypocalcemia, hyperphosphatemia with high PTH level.  Computed tomography scan of head revealed wide spread   calcification in basal ganglia and cerebral hemispheres. X  ray of left foot showed short left 4th metatarsal bone. The  patient was diagnosed as a case of PHP on the basis of  somatic features of AHO with typical biochemical  abnormalities and uncontrolled convulsion with combined  antiepileptic drugs for 16 years. The unusual features in our  case are long delay in clinical diagnosis and absence of family  history. She was treated with calcium salt and vitamin D.  With this treatment patients condition was improved and she  experiences no attack of convulsion and carpal spasm.  Anticonvulsants were withdrawn gradually. We recommend  that hypocalcaemia should be excluded before commencing  anticonvulsant therapy in all epileptic patients and those  patients whose seizures are refractory to anticonvulsant drugs   DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11331   J Bangladesh Coll Phys Surg 2011; 29: 227-230